Systematic Evaluation of a Novel 6-dye Direct and Multiplex PCR-CE-Based InDel Typing System for Forensic Purposes - Fan, Haoliang; He, Yitong; Li, Shuanglin; Xie, Qiqian; Wang, Fenfen; Du, Zhengming; Fang, Yating; Qiu, Pingming; Zhu, Bofeng (Frontiers in Genetics, 2022)
Insertion/deletion (InDel) polymorphisms, combined desirable characteristics of both STRs and SNPs, have considerable potential in the field of forensic practices and population genetics. However, the defects (designed based on non-Asians, long amplicons, et al.) for most commercial InDel kits limited extensive forensic applications in East Asian ancestry (EAS) populations. In the present study, a novel 6-dye direct and multiplex PCR-CE-based typing system was developed based on genome-wide EAS population data and designed to amplify 60 genetic markers (57 A-InDels, 2 Y-InDels, and Amelogenin), simultaneously in a single PCR reaction and detected by capillary electrophoresis. We set up two A-InDel sets to evaluate the forensic performances of the novel system in 1000 Genomes Projects (1KG) populations and Hainan Li. For UAIS (Universal A-InDel Set, containing 44 A-InDels), the cumulative power of discrimination (CPD) ranged from 1-1.03 × 10-14 to 1-1.27 × 10-18 and the cumulative power of exclusion (CPE) varied from 0.993634 to 0.999908. For EAIS (East Asia-based A-InDel Set, including 57 A-InDels), the ranges of CPD and CPE in EAS populations and Hainan Li were 1-1.32 × 10-23 ~ 1-9.42 × 10-24 and 0.999965 ~ 0.999997. What’s more, the population genetic analyses made a relatively clear distinction among intercontinental ancestries groups, and Hainan Li had close relationships with EAS populations. Consequently, the novel 6-dye direct and multiplex PCR-CE-based typing system should be considered as reliable and robust tool for human identification and intercontinental populations inference, and supply additional information for kinship analysis in 1KG populations and Hainan Li.